Nullity of Administrative Acts: Grounds, Legal Regime, Discretion - O. N. Sherstoboev (Сибирское юридическое обозрение, 2021)
The issues of criteria for the nullity of administrative acts are considered, the ratio of an illegal and invalid act, as well as a null and void act, analyzed, the possibility of administrative discretion in determining an invalid administrative act is analyzed, the role of vague legal concepts when an administrative act is declared invalid is demonstrated. The Author uses a comparative legal method, including the analysis of the practice of Germany, Great Britain, South Africa, Canada, Japan, South Korea, Russia and other countries. Special attention is paid to the laws on administrative procedures adopted in the post-Soviet territory and the influence of the German doctrine on this process. It is concluded that for the continental legal order the most preferable way to formalize the criteria for the invalidity of an administrative act are laws on administrative procedures or their analogs, while in the common law states, legal doctrine and judicial practice are of great importance. At the same time, many countries avoid recognizing acts as null and void, preferring the construction of their voidability. This is related to ensuring the stability of public administration, the predictability of administrative activities, and the protection of legitimate expectations. In any case, the theory of the reality of the administrative act is prevailing, and nullity is rather viewed as an anomaly. Therefore, only acts that are adopted with the most significant violations, which do not allow talking about the fair consequences of their adoption, are considered invalid. The illegality of an act does not automatically entail its nullity. A similar trend can be traced in Russia, although individual norms of law and practice of courts indicate the possible formation of a doctrine of the invalidity of an administrative act in the Russian legal system. Insignificant acts do not give rise to consequences from the moment of their adoption, legally they do not exist, and nothing can generate anything. With this approach, the courts only fix the criterion of invalidity without a dispute about law. Insignificant acts should be distinguished from contested ones, the latter may turn out to be illegal, but for a number of reasons (for example, protection of trust) the fact of their existence is confirmed along with their consequences.